Interpolinizacion de variedades de almendro - Herrero, M.=700 1 Cambra, M.; Felipe, A.J.
(Es, En)
Ilus., 6 ref.
Keywords: ARBOLES; POLINIZACION; VARIEDADES; ESPAÑA; ALMENDRO; TUONO; PRIMORSKII; YALTINSKII; ANALES DEL INSTITUTO NACIONAL DE INVESTIGACIONES AGRARIAS